A study on the transfer of radionuclides and of the resulting radiation dose assessment for marine organisms on the eastern coast of Yantai city - Ni, Jialin; Chen, Dongjun; Qian, Zhen; Lin, Jing; Lin, Feng; Ji, Jianda; Huang, Dekun; Yu, Tao (Frontiers in Marine Science, 2024)
Oceans are repositories of radionuclides. Radionuclides are transferred through the food chain and cause ionizing radiation hazards for marine organisms. In this study, the transfer characteristics of 226 Ra, 40 K, 14 C, 3 H, 137 Cs and 90 Sr in organisms at different trophic levels in the eastern coast of Yantai city were investigated. The risk of ionizing radiation to organisms was assessed using the ERICA Tool 2.0. The results show no significant changes in the concentration of any of the nuclides in the coastal area compared to the preoperation period of the nuclear power plant. The transfer factor of 137 Cs, 40 K, 226 Ra, 14 C, 90 Sr and 3 H at the different trophic levels of marine organisms were 2.09, 1.29, 1.17, 1.15, 1.06 and 0.74, respectively. The dose rates of ionizing radiation to organisms from six radionuclides ranged from 32.02 nGy•h -1 to 195.49 nGy•h -1 and had a mean value of 102.86 ± 57.30 nGy•h -1 . The main artificial radionuclides ( 14 C, 3 H, 90 Sr, 137 Cs) released by nuclear power plants in the study area produced negligible radiation doses to marine organisms. However, other artificial radionuclides present in the effluents of nuclear power plants ( 99 Tc, 110m Ag and 131 I) as well as other natural radionuclides (includes 210 Po, 210 Pb, etc) were not included, and further evaluation of these is recommended.